Facilitation of IL-22 production from innate lymphoid cells by prostaglandin E2 prevents experimental lung neutrophilic inflammation. Issue 11 (24th March 2018) - Felton, Jennifer M; Duffin, Rodger; Robb, Calum T; Crittenden, Siobhan; Anderton, Stephen M; Howie, Sarah E M; Whyte, Moira K B; Rossi, Adriano G; Yao, Chengcan
Abstract : Acute lung injury is a neutrophil-dominant, life-threatening disease without effective therapies and better understanding of the pathophysiological mechanisms involved is an urgent need. Here we show that interleukin (IL)-22 is produced from innate lymphoid cells (ILC) and is responsible for suppression of experimental lung neutrophilic inflammation. Blocking prostaglandin E2 (PGE2 ) synthesis reduces lung ILCs and IL-22 production, resulting in exacerbation of lung neutrophilic inflammation. In contrast, activation of the PGE2 receptor EP4 prevents acute lung inflammation. We thus demonstrate a mechanism for production of innate IL-22 in the lung during acute injury, highlighting potential therapeutic strategies for control of lung neutrophilic inflammation by targeting the PGE2 /ILC/IL-22 axis.